(untitled) (Research, Society and Development, 2021)
The packaging protects food from actions of external agents, from alterations and contaminations, in addition to adulteration. Edible films are structures produced from biopolymers, which can replace non-biodegradable packaging. These films have been formulated with naturally polymers of polysaccharides, lipids and proteins, isolated or combined with each other. Edible films produced with polysaccharides and proteins are transparent and flexible, although proteins films are less resistant. They act as a barrier, protecting food and increasing shelf life. Additionally, they can carry antimicrobial and antioxidant compounds, being called active films. The antioxidant power is proportional to the amount of the compound added. Natural extracts such as green tea, cloves, ginger and others can be incorporated into the films, wich could improving the mechanical properties of the films and the characteristics of the food. The use of active edible films has been evaluated in the meat industry as an alternative packaging. This review aims to address the use of edible films added with vegetable compounds, with antimicrobial and antioxidant activity, applied to meat products.